Mental Files and the Theory of Fiction: A Reply to Zoltán Vecsey - Orlando, Eleonora Eva (2021)
In this work I reply to Zoltán Vecsey’s criticisms of the semantic account of fictional names I put forward in Orlando (2017). The main tenet of that proposal is that fictional names refer to individual concepts, which I understand in terms of mental files. In Vecsey (2020), the author presents three main objections: (i) no referential shift can be ascribed to fictional names, (ii) fictional names are supposed to play two conflicting functions, and (iii) the mental file framework is incompatible with an antirealist view of fictional objects. Although the objections are deep and thoughtful, the challenge they involve can be met if certain aspects of the proposal are clarified and developed.